Improving diets in rural Ghana: Food system analysis to identify opportunities for nutrition-sensitive small and medium enterprises - Food and Agricultural Organization of the United Nations; International Food Policy Research Institute; Aberman, Noora-Lisa; Gelli, Aulo; Agandin, John; Kufoalor, Doreen S. (Food and Agricultural Organization of the United Nations, 2021)
This publication presents an in-depth analysis of the food system in Ghana with the dual purpose of providing an overview of the current situation, and identifying opportunities for leveraging the role of small and medium-sized enterprises for nutrition-sensitive food systems. The data collected and the results of the analysis enhance the understanding of some of the challenges that, in the Ghanaian context, contribute to determining diet-related issues; more importantly, the analysis identifies opportunities and entry points for improving diets by overcoming some of the challenges faced by small and medium-sized enterprises. The information provided could be of support not only for further analyses, but also for planning interventions and designing policies to improve nutrition in Ghana and in other contexts.